2003
DOI: 10.1001/archopht.121.10.1452
|View full text |Cite
|
Sign up to set email alerts
|

A Peculiar Autosomal Dominant Macular Dystrophy Caused by an Asparagine Deletion at Codon 169 in the Peripherin/RDS Gene

Abstract: To describe the clinical and genetic findings in a family with a peculiar autosomal dominant macular dystrophy with peripheral deposits. Methods: All family members underwent an ophthalmic examination, and their genomic DNA was screened for mutations in the human retinal degeneration slow (peripherin/RDS) and rhodopsin genes. In selected cases, fluorescein angiography and electrophysiologic testing were performed. Results: The age at onset of the disease was between the third and fourth decades of life, starti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Like prior studies, the phenotype–genotype correlations in this cohort are also difficult to determine (Khani et al, 2003; van Lith‐Verhoeven et al, 2003; Meunier et al, 2011; Roosing et al, 2014; Yang et al, 2003). Shankar et al (2015) reviewed the c.828+3A>T variant and found that 97 patients of 19 different families had diagnoses of RP, macular dystrophy, and PD.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Like prior studies, the phenotype–genotype correlations in this cohort are also difficult to determine (Khani et al, 2003; van Lith‐Verhoeven et al, 2003; Meunier et al, 2011; Roosing et al, 2014; Yang et al, 2003). Shankar et al (2015) reviewed the c.828+3A>T variant and found that 97 patients of 19 different families had diagnoses of RP, macular dystrophy, and PD.…”
Section: Discussionmentioning
confidence: 83%
“…Peripherin‐2 forms oligomeric complexes with other proteins, including the rod outer segment membrane protein‐1 (ROM‐1) and leucine‐rich repeat‐containing protein‐32/glycoprotein‐A repetitions predominant expressed in rods and is critical to the proper formation of the outer segment (Boon et al, 2008; Chakraborty, Conley, Fliesler et al, 2010; Chakraborty, Conley, Stuck et al, 2010; Conley et al, 2010; Ding et al, 2004, 2005; Duncan et al, 2011; van Lith‐Verhoeven et al, 2003; Loewen & Molday, 2000; Poetsch et al, 2001; Poloschek et al, 2010; Tam et al, 2004). The ability to review phenotype–genotype associations within a single rare disorder is advantageous for understanding the phenotypic range and properly categorizing causal genetic variation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The retinal abnormalities range from minor foveal abnormalities to multifocal pattern dystrophy and even retinitis pigmentosa. This remarkable clinical heterogeneity precludes a straightforward genotype–phenotype correlation even with larger patient series 5 8 10 12 16 18 20 29 49. Obviously, modifying factors besides the specific mutation in the peripherin/RDS gene exert an important influence on the resulting phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The rds mouse, which, in genotype, is homozygous for a null mutation in peripherin / RDS , completely fails to develop photoreceptor discs and outer segments, and exhibits down-regulation of rod opsin expression and apoptotic loss of photoreceptor cells (Kohl et al, 1998). Peripherin/RDS mutations in codons 169, 172, and 195 have been identified in autosomal dominant macular dystrophy (Downes et al, 1999;Ekstrom et al, 1998;Lith-Verhoeven et al, 2003b;Nakazawa et al, 1995;Payne et al, 1998;Wells et al, 1993;Yanagihashi et al, 2003). Recently, Khani et al (2003)reported that a RDS mutation in codon 141 is associated with an unusual AMD-like late-onset maculopathy.…”
Section: Spontaneously Gene-mutated (Naturally Mutated) Animal Modelsmentioning
confidence: 99%